Serum interleukin-17 (IL-17) in chronic periodontitis patients - Arief, Erry Mochamad; Mubin, Marina binti; Zainuddin, Siti Lailatul Akmar; Abdullah, Nurul Asma; Ahmad, Basaruddin (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: Explorations into the periodontal medicine relationship have discovered interleukin-17 (IL-17) cytokine as one of the pro-inflammatory mediators that play a crucial role in the initiation and progression of the chronic periodontal disease. This case and control study aimed to compare the serum IL-17 concentration between chronic periodontitis and healthy subjects and to assess the relationship between the IL-17 serum and the clinical periodontal parameters in chronic periodontitis patients. Methods: This study was a case-control study. The subjects were selected using purposive sampling method. The periodontal screening assessment in the Family Treatment Center and Postgraduate Dental Clinic, Universiti Sains Malaysia Hospital. A total of 55 samples who fit with the inclusion and exclusion study criteria of full-mouth clinical periodontal records together with blood serums were obtained from 28 chronic periodontitis patients and from 27 healthy subjects. The concentration of IL-17 cytokine in serum was measured using ELISA test. Results: Subjects with periodontal disease presented significantly worse clinical parameters (p<0.001) compared to control. The level of serum IL-17 concentration was significantly higher (p=0.026) in chronic periodontitis subjects 3.6 (1.03) pg/mL compared to the control 3.1 (0.70) pg/mL. Conclusions: There was no correlation between the level of IL-17 concentration in the serum and clinical periodontal parameters.